Cultural Media in Internet. A Proposed Classification (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
This article proposes a classification of media specialized in culture in Internet that it allows to understand, in the current context of economic crisis and of change of journalistic model, the place that the culture and the cultural journalism occupy in our communicative environment as well as to understand the function that the cultural journalist develops in this context.
Keywords: culture; journalism; mass media; internet